Pengembangan Modul Berbasis Masalah untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa - Soviana, Mita; Gummah, Syifa’ul; Habiburahman, L (IKIP Mataram, 2017)
[Title: The Development of Problem Based Modules to Improve Students' Creative Thinking Skills]. This study aimed to produce a module of physics-based on problems to improve students creative thinking skills. The development model used in this study was ADDIE. This research was conducted in second-grade students of SMP Muhammadiyah Mataram. Data analysis was used qualitative descriptive analysis. The results of this research show that the module rating by validator 1 was 3.28 which criteria into very valid and validator 2 was 3.34 which criteria into very valid. Module practicability was analyzed by the implementation of learning with 3 observers. The assessment by observer 1 was 3.75 very good, observer 2 was 3.75 very good, and observer 3 was 3.79 very good with the criteria of the excellent module assessment. The result of the research shows the students response when used the module was 3.7 is strongly agreed criteria and 3.07 is agreed criteria. The effectiveness of used the module in improving the students creative thinking skills earned an average score of 79.5 with creative criteria. So, it can be concluded that the use of module physics-based problems can be developed feasible used in the learning process.